The importance of reminders and students' performance / Nor Aziah Abd Kadir, Nurul Afzan Najid and Adibah Hussin - Abd Kadir, Nor Aziah; Najid, Nurul Afzan; Hussin, Adibah (2010)
Reminder is a message that helps people remembers something. As the current life style has gotten busier, people have an increasingly hard time to keep track of the many deadlines and due dates that they need to meet in daily life. The purpose of this study is to identify the types of reminders that are mostly preferred by students, to investigate the importance of reminders in students' performance and to analyze the effectiveness of reminders in students' performance. The students' Cumulative Grade Point Average (CGPA) in the last two semesters is used in analysing the improvement in their CGPA. A set of questionnaires has been developed and distributed randomly to 110 students in UiTM Pahang as the respondents. This paper has found support for this prediction based on the data that has been analysed using descriptive analysis. Students need constant and continuous reminders to improve their CGPA. The reminders will be more effective when they increase the salience of specific events such as tests, quizzes, assignments or final examination.